2014
DOI: 10.1371/journal.pgen.1004081
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Molecular Maturation from Peripheral Target Innervation in Nociceptors Expressing a Chimeric TrkA/TrkC Receptor

Abstract: Neurotrophins and their receptors control a number of cellular processes, such as survival, gene expression and axonal growth, by activating multiple signalling pathways in peripheral neurons. Whether each of these pathways controls a distinct developmental process remains unknown. Here we describe a novel knock-in mouse model expressing a chimeric TrkA/TrkC (TrkAC) receptor from TrkA locus. In these mice, prospective nociceptors survived, segregated into appropriate peptidergic and nonpeptidergic subsets, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The genetic tools used to label each of these neuronal populations are MrgD EGFP mice to label MrgD + nonpeptidergic nociceptors (Zylka et al, 2005), Calca(CGRP)-EGFP BAC transgenic mice for peptidergic nociceptors (Bai et al, 2015), Th ; R26 lsl-tdTomato (Ai14) mice (tamoxifen 2 mg/day at postnatal day 13 [P13] to P14) for C-LTMRs (Abraira et al, 2017), TrkB CreER ; Ai14 mice (tamoxifen 2 mg/day at embryonic day 12.5 [E12.5] to E13.5) for Ad-LTMRs (Rutlin et al, 2014), Npy2r-GFP BAC transgenic mice for Ab RA-LTMRs (Li et al, 2011), TrkC CreER ; Ret fGFP mice (tamoxifen 3 mg at E12.5) for Ab SA1-LTMRs (Bai et al, 2015;Jain et al, 2006), TrkC CreER ; Ret fGFP mice (tamoxifen 2 mg/day at P13 to P14) for Ab field-LTMRs (Bai et al, 2015), and PV IRES-Cre ; Ai14 mice to label proprioceptors (Hippenmeyer et al, 2005;Figure 2A). We estimate that these eight populations account for $85% of all DRG neurons (Bai et al, 2015;Gorokhova et al, 2014;Li et al, 2011;Lu et al, 2017).…”
Section: Somatosensory Neurons Exhibit Subtype-specific Intrinsic Membrane Properties and Mechanosensitivitymentioning
confidence: 99%
“…The genetic tools used to label each of these neuronal populations are MrgD EGFP mice to label MrgD + nonpeptidergic nociceptors (Zylka et al, 2005), Calca(CGRP)-EGFP BAC transgenic mice for peptidergic nociceptors (Bai et al, 2015), Th ; R26 lsl-tdTomato (Ai14) mice (tamoxifen 2 mg/day at postnatal day 13 [P13] to P14) for C-LTMRs (Abraira et al, 2017), TrkB CreER ; Ai14 mice (tamoxifen 2 mg/day at embryonic day 12.5 [E12.5] to E13.5) for Ad-LTMRs (Rutlin et al, 2014), Npy2r-GFP BAC transgenic mice for Ab RA-LTMRs (Li et al, 2011), TrkC CreER ; Ret fGFP mice (tamoxifen 3 mg at E12.5) for Ab SA1-LTMRs (Bai et al, 2015;Jain et al, 2006), TrkC CreER ; Ret fGFP mice (tamoxifen 2 mg/day at P13 to P14) for Ab field-LTMRs (Bai et al, 2015), and PV IRES-Cre ; Ai14 mice to label proprioceptors (Hippenmeyer et al, 2005;Figure 2A). We estimate that these eight populations account for $85% of all DRG neurons (Bai et al, 2015;Gorokhova et al, 2014;Li et al, 2011;Lu et al, 2017).…”
Section: Somatosensory Neurons Exhibit Subtype-specific Intrinsic Membrane Properties and Mechanosensitivitymentioning
confidence: 99%
“…Therefore, it is crucial to better understand the precise mechanisms by which NGF leads to mechanical allodynia since anti-NGF drugs have the potential to make a major impact on chronic pain treatment in the near future but are associated with potential adverse events. Interestingly, we have previously shown that our generated knock-in mouse expressing a chimeric TrkAC receptor, formed by the extracellular part of TrkA and the functional transmembrane and intracellular parts of TrkC, the receptor of neurotrophin 3, seems to exhibit a specific deficit in mechanical allodynia but not thermal hyperalgesia following intraplantar CFA injection [16]. Importantly, while nociceptors survival and maturation are normal in the TrkAC adult mice, they present a reduction in peripheral, mostly peptidergic fibers, in the skin.…”
Section: Introductionmentioning
confidence: 95%
“…In the first assay, DRG explants were cultured on Matrigel (Fornaro et al ., ) and stimulated with 2 ml conditioned medium harvested from hydrogels in which 0, 50, 100 or 200 ng VEGF–A165/ml gel were incorporated. As negative and positive controls no GFs or 50 ng NGF/ml medium were added, according to literature data (Deister and Schmidt, ; Gorokhova et al ., ). The conditioned medium used in this assay was F12‐BME.…”
Section: Methodsmentioning
confidence: 98%